Awareness of lean management in construction industry - Norra Azlina, Rohmat (2015)
Nowadays, Malaysian construction industry is growing rapidly. Therefore, more systematic and innovative method has been introduced to the industry to enhance the management and performance of construction project. Lean in construction as discussed by previous researchers is introduced to the construction industry in order to enhance the performance of project and enlarge the contractor’s profit by eliminating waste. According to the past researcher OGC (2007), stated that the purpose of lean in construction is to work on continuous improvement, waste elimination, value for money, high user focus, strong quality management of projects and improved communications. There are two objectives of conducting this research. The first objective of this research is to identify the level of awareness of Lean management among the contractors and finally the second objective is to determine the barriers of implementing the Lean management in Malaysian construction industry. The questionnaire was distributed to the construction industry in Melaka. The result was obtained by using SPSS software. Based on the result, it shows that most of the contractors in Melaka are aware on the implementation of Lean in construction industry.